Identifying young couple issues of families with a parent working abroad vs. traditional families - Calin, Mariana Floricica; Sandu, Mihaela Luminita; Onea, Alexandra (Technium Social Sciences Journal, 2022)
The starting point in the scientific approach of this paper was in the previous research, entitled "Difficulties in the cognitive-emotional development of teenagers with one of the parents who work abroad vs. teenagers with both parents at home”. The subject of children left at home, whose parents went to work abroad is a topic of great interest, which has grown in recent years. Thus, lately, in Romania, more and more children are left "alone" at home because their parents are looking for jobs abroad to ensure an acceptable standard of life for their families. There are many experts who claim that this phenomenon of migration, generates a series of unwanted effects that strongly affects the emotional life of a child. Researchers also say that the most common effects include depression (which can lead to suicide), poor school performance or dropping out of school. Also, it should be noted that the parental departure to work abroad leaves a gap in the child’s life, regardless of his age, whether he is in young age or a teenager. Also, most research on the subject of children with one or both parents working abroad claims that they can develop a wide range of psycho-behavioral manifestations, including: feeling abandoned sadness, anxiety, insecurity, depression, aggressive behavior or indifference, poor school behavior, poor concentration, over / underestimation, self-isolation, apathy, lack of motivation, delinquent behaviors. The research was successful in the sense that all the hypotheses were confirmed, which obviously aroused our curiosity to investigate further and find out what imprint is missing from one of the parents in the life of the child, who became an adult and more, on the verge of starting his own family. Thus, this paper aims to identify the difficulties encountered by those who come from families with a departed parent, in the life of the couple.